KLASIFIKASI KATA DALAM BAHASA ARAB MENURUT LINGUIS ARAB KLASIK DAN MODERN - Abdul Basith (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
This paper aims to investigate Arabic word classificati based on Arabic Grammarians and modern linguists’ perspectives and principles which they use in that classification. As it is explored by Arabic Grammarians, the word classification is divided into three components, such as ism (noun), fi'l (verb) and harf (particle) ,which causes problems when between definition and sign of each of the classification is unmatched in a given text. Therefore, some modern linguists, one of them is Tamām Hassān, try to reconsider and to remake a new classification of Arabic words. While other Arabic Grammarians only use the six principles of classification (such as distribution principle, substitution principle, function principle, morpheme principle, meaning principle and predicative principle), Tamām Hassān uses two additional principles, those are: the form principle (al-mabnā) and the meaning principle (alma'nā). and the conclusion of is that Arabic word is divided to seven such as ism (noun), sifah (adjective), fi'l (verb), damīr (pronoun),  arf (adverb), khalīfah (exclamation) and adāh.